NATURAL FACTORS AND THEIR IMPACT ON THE URBANIZATION OF AGRICULTURAL LAND IN KIRKUK DISTRICT CENTER FOR THE PERIOD (1997-2018) - Layla Ali Abd Ahmed, Dafer Abrahem Taha; Layla Ali Abd Ahmed, Dafer Abrahem Taha (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The area of agricultural land and its productivity decreases day by day. Also, its profits obtained are reduced compared to other trades due to natural or human causes. This reduces the desire of farmers to do agriculture and change to other occupations. This, the land is left leave without agriculture or is converted to other uses. This is known as the emergence of urbanization in agricultural land which may vary according to the appropriateness of natural factors for expansion, especially in the center of Kirkuk district. Then, this districts uffers from the variation in the natural characteristics. There is also a lack in the interest in the agricultural especially after the discovery of Oil, whose revenues represent the basis in raising the national income of the population compared to agriculture. So this study dealt with three investigations specialized the first specialized in the study of the natural characteristics of the terrain, its suitability for expansion and the quality of water and types of soil suitable for urban construction.The second topic dealt with the study of the stages of urbanization expansion during 1997-2018 and the rate of change in the area of agricultural land within the third research.